If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 90 = 85 Reorder the terms: 90 + 12x = 85 Solving 90 + 12x = 85 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + 12x = 85 + -90 Combine like terms: 90 + -90 = 0 0 + 12x = 85 + -90 12x = 85 + -90 Combine like terms: 85 + -90 = -5 12x = -5 Divide each side by '12'. x = -0.4166666667 Simplifying x = -0.4166666667
| a+3b=-2 | | 7(y-6)=28 | | 5.6+10.5=2.1A | | 8x^2+22x=-5 | | 11x-20=7x-64 | | -(1-7x)-6(-7-x)=36 | | 7x+35=-21 | | 13+2d+4d+3d+9= | | -16b=9 | | y=x^2-6x-3 | | 26+b=20 | | -8x-9x=.66 | | 2a=18 | | 12=x^2-6x | | 3x+9-x=15 | | 36x^2-9x=0 | | 10x^2-8x+1=0 | | 10x^2=58 | | 19x^2=58 | | 24a-22=-49(1-6a) | | 3x+11=-1 | | 16x-3=102-5x | | 107-14-6y=-2(y-4y) | | 60-2x+70-4x=180 | | 4/5/10/6= | | h=3+65t-16t^2 | | h=-16t^2+65t+3 | | -35=-7(5p-5)-5(4p+3) | | -52=-8(4-5n)-4(n-4) | | -1+x^2-1x=0 | | 4(-7+2m)+4(1-m)=-36 | | (80-x)+(90-2x)=180 |